Prevalence and determinants of metabolic syndrome among newly diagnosed type 2 diabetic subjects according to different criteria. Issue 2 (April 2015) - Hossain, Sharmin; Fatema, Kaniz; Ahmed, Kazi R.; Akter, Jesmin; Chowdhury, Hasina A.; Shahjahan, Md; Acharyya, Amitava; Rahim, M.A.; Ali, Liaquat
Abstract Background and aim Metabolic syndrome (MS) is becoming a serious global public health problem. The prevalence of MS differs in different population by using different definitions. Present study aimed to find out the prevalence and determinants of MS among newly diagnosed type 2 diabetes (NDT2D) according to different criteria. Subjects and methods This cross-sectional analytic study was conducted among 281 subjects selected purposively from the OPD of BIRDEM. Information on lifestyle factors and disease history were collected using a semi-structured questionnaire by face to face interview. The three definitions of MS used in this study are from the International Diabetes Federation (IDF), a modified version of the ATP III criteria for Asian populations (modified ATP III) and World Health Organization (WHO) criteria. Adjusted odds ratio and confidence limit were generated through logistic regression. Results The overall prevalence of metabolic syndrome among the study subjects according to modified ATPIII, WHO and IDF criteria were 79% (95% CI: 74.2-83.8), 81% (95% CI: 76.4-85.6) and 68% (95% CI: 62.6-73.5) respectively. The prevalence of metabolic syndrome among female were higher compared to males in all the criteria's. Female gender (OR = 5.93), family history of diabetes (OR = 1.92), overweight (OR = 6.2), and obesity (OR = 5.13) were found as important confounders associated with metabolic syndrome. Conclusion The prevalence of the metabolic syndrome among NDT2D is considerably higher in our population which may indicate considerable risk of cardiovascular diseases in future. Female gender, family history of diabetes, overweight and obesity are important confounders of MS in this population.